1989
DOI: 10.1021/j100345a079
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR spectroscopy of benzene adsorbed on .eta.-alumina

Abstract: peak at 304 nm, and the corresponding fluorescence spectra were broad and featureless with a maximum at 395 nm and a lifetime of 55 ns. The absorption spectra were consistent with a disordered, glasslike adlayer, and the broad featureless fluorescence spectra were attributed to excimer emission. The relatively long 55-11s fluorescence decay times were also consistent with excimer emission.The absorption spectra changed abruptly and resembled the crystalline absorption spectra when the adlayer was annealed to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is not clear exactly how C 6 F 6 interacts with the alumina surface. Benzene coordinates via π-electrons to act as a proton acceptor or π-donor . Hexafluorobenzene on the other hand has been shown through ab initio calculations and spectroscopic investigations to act as a lone-pair acceptor and interacts with the oxygen center of H 2 O, , and it is a reasonable proposition that this type of interaction can also take place on the surface of alumina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear exactly how C 6 F 6 interacts with the alumina surface. Benzene coordinates via π-electrons to act as a proton acceptor or π-donor . Hexafluorobenzene on the other hand has been shown through ab initio calculations and spectroscopic investigations to act as a lone-pair acceptor and interacts with the oxygen center of H 2 O, , and it is a reasonable proposition that this type of interaction can also take place on the surface of alumina.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, an amorphous alumina surface must be a very complex mixture of these possibilities. Adsorption of aromatic molecules to the surface of alumina is believed to occur through interaction of the aromatic π-system with hydroxyl and Al 3+ centers at the oxide surface …”
Section: Introductionmentioning
confidence: 99%
“…in CO on transition metals. [26][27][28] On the other hand, several studies [29][30][31][32][33][34] have shown that for carbon not directly bonded to the metal, e.g. separated by a heteroatom such as S 30 or physisorbed, [32][33][34] the change in peak position is more moderate, < 20 ppm, and can be used to monitor adsorption.…”
mentioning
confidence: 99%
“…[26][27][28] On the other hand, several studies [29][30][31][32][33][34] have shown that for carbon not directly bonded to the metal, e.g. separated by a heteroatom such as S 30 or physisorbed, [32][33][34] the change in peak position is more moderate, < 20 ppm, and can be used to monitor adsorption. [29][30][31][32][33][34] One recent study demonstrated that the chemical shift of formate on different metal nanoparticles correlated well with the calculated dband center, formate decomposition rate, metal work function, and specific activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation